2022
DOI: 10.1007/s00572-022-01079-0
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi and production of secondary metabolites in medicinal plants

Abstract: Medicinal plants are an important source of therapeutic compounds used in the treatment of many diseases since ancient times. Interestingly, they form associations with numerous microorganisms developing as endophytes or symbionts in different parts of the plants. Within the soil, arbuscular mycorrhizal fungi (AMF) are the most prevalent symbiotic microorganisms forming associations with more than 70% of vascular plants. In the last decade, a number of studies have reported the positive effects of AMF on impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 294 publications
(299 reference statements)
0
31
0
1
Order By: Relevance
“…Additionally, TiO 2 nanoparticles help to convert inorganic N into organic N in the form of protein and chlorophyll, which leads to an increase in the photosynthetic rate [40]. Zhao et al [41] noted that the increase in primary photosynthesis compounds including erythrose-4-phosphate, phosphoenolpyruvate, pyruvate, and glyceraldehyde-3-phosphate plays a main role in increasing terpene constituents and EO productivity in medicinal and aromatic plants. In addition, Hazzoumi et al [42] concluded that AMF inoculation stimulates the productivity of EO glands probably by increasing endogenous hormone levels, particularly cytokinin, indole-3-acetic acid, and gibberellin.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TiO 2 nanoparticles help to convert inorganic N into organic N in the form of protein and chlorophyll, which leads to an increase in the photosynthetic rate [40]. Zhao et al [41] noted that the increase in primary photosynthesis compounds including erythrose-4-phosphate, phosphoenolpyruvate, pyruvate, and glyceraldehyde-3-phosphate plays a main role in increasing terpene constituents and EO productivity in medicinal and aromatic plants. In addition, Hazzoumi et al [42] concluded that AMF inoculation stimulates the productivity of EO glands probably by increasing endogenous hormone levels, particularly cytokinin, indole-3-acetic acid, and gibberellin.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the impact of Cs-NPs on dry matter retention during drought stress could be related to the reduction in transpiration induced by the closure of the stomata [18]. Moreover, the inoculation of mycorrhizal fungi with host plant roots improves the plant performance directly through increasing nutrient and water uptake and indirectly by plant phytohormonal secretions of gibberellic acid, cytokinins and jasmonic acid [52]. It was reported that inoculation of mycorrhizal fungi in thyme roots enhanced plant productivity through improving macro-and micro-nutrient uptake under drought stress conditions [14].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the co-application of Cs-NPs+ Myco-Root improves the photosynthetic rate, along with the nutrient accessibility, which have an important role in the production of carbohydrates and also in the development of glandular trichomes, EO channels and secretory ducts [13]. In this situation, the higher photosynthetic rate enhances the concentration of primary metabolites such as pyruvate, erythrose-4-phosphate, phosphoenolpyruvate and glyceraldehyde-3-phosphate, which are used as precursors in the synthesis of EO constituents [52].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AMF can furnish host plants with vital inorganic nutrients, resulting in increased growth and yield under both unstressed and stressed conditions [ 19 ]. Despite their enormous potential to improve plant growth under climatic stresses, little is known about how AMF-induced modulations in tolerance mechanisms, as well as the crosstalk triggered to regulate plant performance, can help increase crop productivity [ 24 , 25 ], especially for the majority of previously overlooked leguminous species.…”
Section: Introductionmentioning
confidence: 99%